Advances in Physalis molecular research: applications in authentication, genetic diversity, phylogenetics, functional genes, and omics - Jiang, Yan; Jin, Yanyun; Shan, Yiyi; Zhong, Quanzhou; Wang, Huizhong; Shen, Chenjia; Feng, Shangguo (Frontiers in Plant Science, 2024)
The plants of the genus Physalis L. have been extensively utilized in traditional and indigenous Chinese medicinal practices for treating a variety of ailments, including dermatitis, malaria, asthma, hepatitis, and liver disorders. The present review aims to achieve a comprehensive and up-to date investigation of the genus Physalis, a new model crop to understand plant diversity and fruit development. Several chloroplast DNA-, nuclear ribosomal DNA-, and genomic DNA-based markers, such as psbA-trnH, internal transcribed spacer (ITS), simple sequence repeat (SSR), random amplified microsatellites (RAMS), sequence-characterized amplified region (SCAR), and single nucleotide polymorphism (SNP) were developed for molecular identification, genetic diversity and phylogenetic studies of Physalis species. A large number of functional genes involved in inflated calyx syndrome development (AP2-L, MPF2, MPF3, and MAGO), organ growth (AG1, AG2, POS1, and CNR1), and active ingredient metabolism (24ISO, DHCRT, P450-CPL, SR, DUF538, TAS14, and 3β-HSB) were identified, contributing to the breeding of novel Physalis varieties. Various omic studies revealed and functional identified a series of reproductive organ development-related factors, environmental stress responsive genes and active component biosynthesisrelated enzymes. The chromosome-level genomes of Physalis floridana Rydb., P. grisea (Waterf.) M. Martínez and P. pruinosa L. have been recently published, providing a valuable resource for genome editing in Physalis crops. Our review summarizes the recent progress in genetic diversity, molecular identification, phylogenetics, functional genes, and the application of omics of in the genus Physalis and accelerates efficient utilization of this traditional herb.